Association between the -455T>C promoter polymorphism of the APOC3 gene and the metabolic syndrome in a multi-ethnic sample - Hanley Anthony JG; Harris Stewart B; Zinman Bernard; Yusuf Salim; Anand Sonia S; Bjerregaard Peter; Young T Kue; Ban Matthew R; Pollex Rebecca L; Connelly Philip W; Huff Murray W; Hegele Robert A (BMC, 2007)
Abstract Background Common polymorphisms in the promoter of the APOC3 gene have been associated with hypertriglyceridemia and may impact on phenotypic expression of the metabolic syndrome (MetS). The rs7566605 marker, located near the INSIG2 gene, has been found to be associated with obesity, making it also a potential genetic determinant for MetS. The objective of this study is to examine the APOC3 -455T>C and the INSIG2 rs7566605 polymorphisms as potential genetic determinants for MetS in a multi-ethnic sample. Methods Subjects were genotyped for both the APOC3 -455T>C and INSIG2 rs7566605 polymorphisms, and classified for the presence or absence of MetS (NCEP ATP III and IDF definitions). The total study population included 2675 subjects (≥18 years of age) from six different geographical ancestries. Results For the overall study population, the prevalence of MetS was 22.6% (NCEP ATP III definition). Carriers of ≥1 copy of APOC3 -455C were more likely to have MetS (NCEP ATP III definition) than noncarriers (carrier odds ratio 1.73, 95% CI 1.40 to 2.14, adjusting for age and study group). The basis of the association was related not only to a higher proportion of -455C carriers meeting the triglyceride and high-density lipoprotein cholesterol criteria, but also the blood pressure criteria compared with wild-type homozygotes. Plasma apo C-III concentrations were not associated with APOC3 -455T>C genotype. The INSIG2 rs7566605 polymorphism was not associated with MetS or measures of obesity. Conclusion Meta-analysis of the sample of multiple geographic ancestries indicated that the functional -455T>C promoter polymorphism in APOC3 was associated with an approximately 2-fold increased risk of MetS, whereas the INSIG2 rs7566605 polymorphism was not associated with MetS.